160 Steers inoculated with Salmonella exhibit dissimilar hematology and body temperature profiles based on their exposure to a synthetic glucocorticoid. (29th July 2019) - Wilkerson, Shannon R; Broadway, P Rand; Carroll, Jeffery A; Burdick-Sanchez, Nicole; Tigue, Daniel A; Rehm, John G; Callaway, Todd R; Bratcher, Christy L
Abstract: The objective of this study was to determine the effects of daily dexamethasone (DEX) infusions on hematology and body temperature in response to experimental, oral inoculation with Salmonella typhimurium. Weaned Holstein steer calves (n = 20; BW=102±2.7 kg) received DEX (n = 10; 0.5mg/kg BW) or saline (CON; n = 10; 0.5mg/kg BW) for 4 d (from d -1 to d 2) while simultaneously receiving an oral inoculation of a naldixic acid resistant Salmonella typhimurium (3.4x106 CFU/animal) via milk replacer on d 0. Fecal swabs for SAL shedding were obtained daily and samples were confirmed positive starting 24 h post inoculation (d 1) to harvest (d 5). Dexamethasone (DEX) administration was achieved via indwelling jugular catheters which were fitted simultaneously with rectal temperature (RT) recording devices on d −2 relative to inoculation and placed in individual pens in an environmentally controlled facility. Whole blood was collected at -24, -12, and 0 h; and at 8-h intervals from 8 to 120 h for hematology. There was a time x treatment (There should be) for RT such that the DEX treatment resulted in a decreased RT on d -1 to 2. A treatment × time interaction (P < 0.05) was observed for total white blood cells (WBC), neutrophils, lymphocytes, eosinophils, and monocytes. Specifically, DEX increased WBC and neutrophils in DEX steers (P < 0.0001) yet lymphocytes increased following DEX administration (P < 0.05 at 24 and 48 h, respectively). Monocytes initially increased (P < 0.001) in response to the -24 h DEX treatment but slowly decreased beyond CON group levels following the 48 h DEX treatment. These data may be interpreted as either mimicking multiple acute stressors with respect to daily DEX injections, mild immunosuppression due to multiple DEX exposures, or a combination of both scenarios when juxtaposing DEX and Salmonella inoculation.